EXPRESSION OF ANGIOTENSIN-CONVERTING ENZYME-2 IN LUNG TISSUES IN EXPERIMENTAL BRONCHOPNEUMMONIA - Ziablitsev, D.S.; Dyadik, O.O.; Khudoliy, S.О.; Shepitko, V.I.; Ziablitsev, S.V. (World of Medicine and Biology, 2021)
The purpose of this study was to establish the effect of acute pulmonary inflammation of non-viral origin on the expression of angiotensin-converting enzyme-2. Wistar rats (n=20) were introduced into the trachea of sterile nylon thread 2.5 cm long and 0.2 mm thick to a depth of 2.5 cm. Endotracheal injection of nylon thread led to formation of acute bronchopneumonia, which included the sequential development of: exudative and proliferative inflammation, peribronchial and alveolar abscesses, their organization and diffuse fibrosis of the lung parenchyma. It was shown that the exudative phase of acute inflammation was accompanied by inhibition of angiotensin-converting enzyme-2 expression in bronchial epitheliocytes, type II alveolocytes and vascular endothelium. During the transition of inflammation to the stage of proliferation and fibrosis, the expression of the enzyme was restored. The identified changes indicated the presence of regulatory factors that differ from the coronavirus action.
Keywords: acute inflammation; fibrosis; endotracheal injection; immunohistochemistry